Peningkatan Cakupan ASI Eksklusif melalui Program Edukasi “GENDIS” (Generasi Emas dengan ASI Eksklusif) di Kecamatan Sambi, Kabupaten Boyolali - Selviana, Tasya Ardia; Ma'mun, Wafa; Putri, Salsabila Nur Azizah Harinda; Septiana, Risda; Safitri, Retno; Lestari, Anik; Andarwati, Dwi Astuti Dian (Jurnal SOLMA, 2024)
Background: In 2023 the coverage of exclusive breastfeeding for infants aged 6-23 months in Indonesia was 55.5%, while the national target was 75%. The coverage of exclusive breastfeeding in Boyolali Regency reached 79,1% in 2022, but in Sambi Subdistrict It was only 50,5% in 2024 indicating that this figure did not meet the national target. The aim of this program is to increase the coverage of exclusive breastfeeding in Puskesmas Sambi, Boyolali Regency’s working area. Method: The method used was community nutrition education based on the result of problem analysis using problem solving cycle from primary and secondary datas. The program ‘s success was assessed by the difference between average pre-test and post-test score. Result: Based on the results, the average pre-test score was 77,78 and the average post-test score was 83,65. It showed an increase of 5,87 for the average score. The statistical test found a significant difference between average pre-test and post-test scores with p = 0.020 (p < 0.05). Conclusion: Education using lecture also question and answer discussion combined with several medias such as leaflet, recipe book, videos, and practice tool in "GENDIS (Generasi Emas dengan ASI Eksklusif)" education program succeeded in increasing participants’ knowledge about exclusive breastfeeding practice solution for working mothers.